LEVANTAMIENTO Y DISEÑO DEL PROCESO DE ELABORACIÓN EN EL ÁREA DE FABRICACIÓN DE MONTERREY AZUCARERA LOJANA C.A. DEL CANTÓN CATAMAYO, PROVINCIA DE LOJA - Benitez Avila, Karen Estefanía (2020)
he purpose of this research work is to carry out a survey and design of the manufacturing process in the manufacturing area of Monterrey Azucarera Lojana C.A. of the canton Catamayo, province of Loja, through the three main phases of the process management model according to the methodology presented by the author Jaime Cadena, such as: elaboration of a process map, gathering information and design of the process, through the survey of activities, flow charts, characterization of the process and the procedures manual. The following methods were used to carry out the work: descriptive in the current situation of the activities of the sugar manufacturing macroprocess, the synthetic method in the development of the results, the deductive method in the construction of the literature review and the inductive method In the discussion of the results, techniques such as the interview with the Head of the Plant and the Head of the Quality Control Laboratory, and direct observation with the aim of having a knowledge of the current situation of the process were also used. The results show the lifting of the activities using the observation guides. It should be noted that the research focuses on the manufacturing process, but it was necessary to describe the inputs to the process, representing the manufacture of sugar as a macroprocess, as the reception of cane, preparation of cane, milling and extraction, and elaboration processes, this in turn with eight threads such as purification, evaporation, clarification of the cheek, crystallization, exhaustion, spinning, drying and packaging. Thus, it is concluded that the technical sheets are control tools in order for the company to have an information medium for the manufacturing process; The restructuring and updating of the sugar manufacturing procedure manual will allow acting on each procedure established for the development of the manufacturing macroprocess, these activities are carried out in an approximate time of 8 hours. In addition, it is proposed to update the procedures manual whenever there are variations in activities, either due to its legal regulations or another aspect.